Comparison of 10-year atherosclerotic cardiovascular disease (ASCVD) risk in metropolitan and rural areas of South of Iran - Mohammad Javad Zibaeenezhad; Mehrab Sayadi; Hossein Pourmontaseri; Davood Khalili; Mojtaba Farjam; Ehsan Bahramail; Nader Parsa; Azizallah Dehghan; Seyyed Saeed Mohammadi; Iman Razeghian-Jahromi; Hamed Bazrafshan drissi; Matin Sepehrinia (Scientific Reports)
Abstract The first step to reducing the growing burden of cardiovascular disease (CVD) is to find modifiable risk factors with the highest burden in each population. Urban and rural citizens may have different priorities in this regard. This study aimed to compare the 10-year incidence probability of CVD events and its associated risk factors between rural and urban areas in Iran. Data was extracted from two big cohorts, Fasa Adults Cohort Study (FACS) and Shiraz Heart Study (SHS), with participation of over 12,000 general population. Linear regression models were used to test the difference in CVD risk between two populations. Totally, 6,258 FACS and 6,101 SHS participants entered the study. Urban participants had a significantly higher mean ASCVD score (4.43% vs. 5.51%, p-value < 0.001). Also, they significantly showed higher body mass index, waist circumference, cholesterol level, fasting blood glucose level, systolic blood pressure, educational attainment, and occupational status. However, the prevalence of smoking was higher in rural areas. Notably, socioeconomic parameters including marital, occupational, and educational statuses seem to have strong impact on cardiovascular risk factors. After adjustment for all confounders, living in the urban areas seemed to be associated with higher atherosclerotic CVD risk (β = 0.78, 95%CI: [0.69–1.05]), which was consistent across both sexes. Given the higher risk of cardiovascular events in urban areas and different profiles of risk factors between these two regions, preventive strategies should be precisely and separately designed for each population by the health authorities and policymakers in order to reduce the CVD toll efficiently.